The Firefighters’ Referendum - Should Questions arising from Industrial Disputes be excluded from a Referenda held under the Citizens Initiated Referenda Act 1993? - Wehrle, G (Victoria University of Wellington Law Review, 1997)
The New Zealand Professional Firefighters’ Union initiated the first referendum held under the Citizens Initiated Referenda Act 1993. This article examines the question whether that referendum demonstrated a need to reform the Act to restrict the subject-matter of future referenda under the Act. The analysis is conducted in the context of the history and aims of the Act and of the firefighters’ dispute. The article a case study of New Zealand’s first citizen initiated referendum.